Evaluation of physical fitness in wheelchair badminton athletes - Time analytics from international para-badminton WH1 singles games - Warashina, Y. (The Journal of Physical Fitness and Sports Medicine, 2020)
Background: detailed performance analytics of para-badminton athletes has not been revealed. Especially in wheelchair class, due to the characteristics of the competition, it is necessary to use the upper limbs to drive the wheelchair, hit the shuttle and brake the wheelchair in order to hit a single stroke, and this process must be continued continuously and intermittently. As a result, the risk of injury to the upper limbs including the shoulder joint is high, but the international required physical fitness level is not yet clarified. [Purpose] The purpose of this study was to clarify the physical fitness standard required of para-badminton WH1 athletes through time analytics from international para-badminton WH1 singles games at the upper levels. [Methods] We selected matches between the top 10 ranked players in the WH1 class in the world (898 in-nings in all) and recorded WP (working period | rally time in seconds) and RP (resting period | rest time in seconds) and stroke numbers in each inning. [Results] The average WP per inning was 8.9 seconds (0.9-62.3 seconds), the average RP was 12.7 seconds (1.0-57.7 seconds), and the average number of strokes per inning was 7.0 (1-48); the WP/RP was 0.7 and the stroke tempo was 1.3 strokes per second. [Conclusions] As an international benchmark of physical fitness in the WH1 singles event of Para-badminton, the players are required to compete with each other at a rate of one hit per second for the entire match, with a W:R ratio of 1:1.4 intermittent exercise, and to continue to do so for about 7 hits.